ATTITUDES TOWARD FARM ANIMALS WELFARE AND CONSUMERS BUYING INTENTIONS - CASE OF SERBIA - Veljković, Saša; Stojanović, Žaklina; Filipović, Jelena (Economics of Agriculture, 2015)
The aim of this study is to examine consumers perception of the products considering animal welfare and to establish the factors which affect consumers willingness to pay the premium price for the animal-friendly products. In addition, four consumers profiles according to their attitudes towards farm animals welfare are distinguished and their features are elaborated. The research has been undertaken in Belgrade, comprising 198 participants. The face-to-face interview technique has been adopted, while for the analysis of the results regression and cluster analyses have been performed. The findings suggest that food sector stakeholders should put more efforts in providing information and education to the consumers regarding the importance of animal welfare and that there is a significant market potential for the introduction of the label for animal-friendly products. The implications for policy makers are proposed and discussed too.